Sustainability and environmental change in a small company in the pharmaceutical marketing industry. (2015) - Murphy, Charles J.; Middleton, Vikki C.
Small companies, and large companies alike, are subject to significant changes in their external environments. This case study describes the critical events confronting a small company which led to the need for managers to scan its environment in order to better understand the environmental complexity of their industry. By first analysing the environment, the company was able to gain insight regarding many potential strategic factors that could possibly lead to the company becoming a sustainable entity in the pharmaceutical marketing industry. But having developed the information about the industry is just the beginning. The company realises it must now face questions of which are the appropriate models and techniques to use for organising the environmental scan, and how to apply them in this situation. They also want to have the scanning results become the basis for beginning the process of developing a strategic plan. Lessons to be learned include those related to environmental scanning and strategic modelling.